1994
DOI: 10.1080/758536232
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Tendering and Contracting in the Public Sector: A Survey

Abstract: This paper is a survey of the role and impact of competitive tendering and contracting (CTC) policies in the public sector. The paper examines the theoretical rationale for introducing competition in the provision of public services and the methodology by which contracting decisions are reached. It investigates the extent of implementation and nature of outcomes in several countries. A broad sweep of the empirical findings suggests that CTC generates substantial cost savings. Lack of adequate data makes an ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
80
0
5

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(87 citation statements)
references
References 20 publications
2
80
0
5
Order By: Relevance
“…Early academic analyses of the effect of privatization on costs usually found a positive relation between privatization and cost savings. Similar results were stressed in reviews such as Domberger and Rimmer (1994) and Domberger and Jensen (1997).…”
Section: Introductionsupporting
confidence: 71%
“…Early academic analyses of the effect of privatization on costs usually found a positive relation between privatization and cost savings. Similar results were stressed in reviews such as Domberger and Rimmer (1994) and Domberger and Jensen (1997).…”
Section: Introductionsupporting
confidence: 71%
“…Evidence of the effect on service quality has been much more limited. Those studies that do exist have typically found mixed results (Domberger and Rimmer, 1994;and Boyne, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Similar initiatives have been introduced elsewhere (Domberger and Rimmer, 1994). Sturgess et al (2007a and2007b) provide a recent comprehensive survey.…”
Section: Introductionmentioning
confidence: 99%
“…As a rule, costs savings have been found and their magnitude is important (see the reviews by Domberger and Rimmer 1994, Boyne 1998, and Andrews 2011.…”
Section: Introductionmentioning
confidence: 99%